Incineration bottom ash geopolymer aerated concrete - Rao, Xue Hong (2015)
Aerated concrete is a type of porous construction materials that are extremely light-weight. Due to their porous nature, aerated concrete is known for their thermal and sound insulation. These sophisticated concrete are traditionally produced from OPC cement and aluminum powder being the aerating agent. To further enhance the sustainability of such green concrete, OPC cement and aluminum powder can be substituted with metakaolin geopolymer and Incineration bottom ash (IBA). Geopolymer forms the binder agent of the concrete while IBA act as the aerating agent. IBA is found to be a hazardous by-product from municipal solid waste incineration which contains amount of metallic aluminium in composition. Geopolymer on the other hand is used for application to immobilise toxic substances. Geopolymer and IBA can thereby complement each other in production of aerated concrete. The process of making IBA aerated concrete depends on few factors namely; geopolymer mix design, aerating capacity of IBA, aerating characteristic of IBA, yield stress and setting time of the IBA paste. Experiments are specially designed to address these factors. Waterglass SiO2: Al2O3 3.2 mix design is found to provide a highest compressive strength of 50MPa. IBA has proven to be able to replace Aluminium as aerating agent. Aerating capacity of Aluminium to IBA is approximate 1: 250 times. IBA has significantly impact on the increase of yield stress which is advantageous to the making of light-weight geopolymer aerated concrete (GAC). Yield stress is found to be the paramount factor on the ability to capture air and prevent the collapse of air voids in aerated concrete. Pore structure has been observed under the microscope to reveal characteristic of pores formation. In a nut shell, IBA produced GAC produced with higher compressive strength than aluminium GAC. Minimum density of IBA GAC produced in the study is 0.86g/cm3 with a compressive strength of 5.49 MPa. Pores size observed in the IBA GAC matrix are relatively smaller and higher in quantity from compared to Al GAC matrix. However, thermal conductivity in IAC is the only drawback as it tends to give a higher value of GAC in density ranges more than 0.9g/cm3. Minimum thermal conductivity IBA GAC produced in the study is 0.33W/mK. Further test were recommended to improve the image capturing capability of the microscope and pore size distribution analysis. Pores capturing technique need to further enhanced in view to produce conclusive results. Impregnation of pores with epoxy resin may be a viable solution. However trial tests have revealed that method has several problems need to be addressed. Toxic characteristic leaching procedure (TCLP) of IAC is other area that studied as it shall conclude if IBA GAC is suitable for human exposure.